A Strategic Analysis of Allegro: A Custom Made Supply Chain Management Software - Rasjid, Zulfany Erlisa (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Allegro is a Supply Chain Management software which is used by one of the Buying Agent that has branches all over the world. Allegro is a tailor-made application specially build for the Buying Agent. Allegro thas a lot of capability, however it is not being used optimally. This paper analyszes the software such that it can be used optimally to support the company (Buying Agent) strategically and help the company to perform better by using Balance Score Card and KPI generated by the use of the system. The KPI is derived from the Business Objectives and the data in fact are all available in Allegro which is currently not used. As a conclusion, the writer suggested using all features available from Allegro and hence it will prove the overall performance of the company.